Decolonising Science Education: A Bibliometric Analysis of Indigenous Knowledge Integration in Global STEM - Gunawan, Kadek Dwi Hendratma; Indrawan, I Putu Oktap (Journal of Posthumanism, 2025)
This study presents a systematic bibliometric review of research on Indigenous knowledge integration within global STEM education between 2015 and 2025. Using keyword co-occurrence mapping and cluster analysis, the study identifies thematic patterns, research trajectories, and conceptual gaps in the emerging discourse on decolonizing science education. The findings reveal that integration efforts remain fragmented, often limited to isolated case studies or tokenistic curriculum adaptations. Genuine transformation requires coherent frameworks that position Indigenous epistemologies as foundational rather than peripheral to scientific inquiry. The study highlights the critical need for community collaboration, contextualised pedagogy, and systemic reform to foster epistemic justice and educational equity. By mapping current research landscapes, this review contributes to advancing more inclusive and pluralistic models of science education worldwide.